The Effectiveness of the Sports Game Approach in Improving Gross Motor Skills of SB At-Tanzil Ampang Malaysia Students - Nur’anisah, Nur’anisah; Nur, Hana Astria; Hadiana, Oman; Heriyana, Tio; Manan, Nanan Abdul (Jurnal Pendidikan Jasmani (JPJ), 2024)
Physical education, sports, health is a physical activity contained in the curriculum at every school level. There are 3 important aspects in health sports physical education, namely affective, cognitive and psychomotor aspects. This research aims to improve motor skills in SB At-Tanzil Ampang students by introducing sports games and traditional games. Such as jumping rope, gobak sodor and other sports games. This study uses an experimental method with a one-group pretest posttest research design. The result of this study is that the game approach has significant results in improving gross motor skills in SB At-Tanzil Ampang students, so that the game approach is effective to be used as one of the learning methods.